(untitled) (One Health Journal of Nepal, 2021)
Introduction: Emergency contraceptives prevent unintended pregnancy which reduce unsafe abortion or unwanted child birth. Very few undergraduates are aware of it which can be considered as major problem of maternal health. The main aim of the study was to find out the level of existing knowledge of emergency contraceptives among undergraduate’s students. Methods: A descriptive cross-sectional study was carried out in Bhojpur Multiple Campus, Province 1. Ethical approval was obtained from Nepal Health Research Council (Reg. no. 386/2019). Data was collected from 360 students, selected by convenient method. Validated and pretested self-administered questionnaire was used to find out knowledge regarding emergency contraceptives. The data was entered and analyzed in SPSS V 16. Descriptive statistics was reported using frequencies and percentages. Results: The findings of study revealed that among 360 respondents, more than half 237 (65.8%) of the respondents had heard about emergency contraceptives. Out of 237 respondents, 66.2% were found to have good knowledge regarding emergency contraceptives. 38.4% respondents reported emergency contraceptive as a drug used for birth spacing, only 6.3% respondents were aware about intrauterine device. Conclusions: Based on the study findings, knowledge of emergency contraceptives among college students was low. More than half of the respondents had poor knowledge of emergency contraceptives which provide an assumptive severity of the problems of unintended pregnancy and unsafe abortion.